The effect of framework fabrication technique on the fit accuracy of full arch screw retained implant supported prostheses - Fellwa AlRasheed; Khalid AlWazzan (Elsevier, 2022)
Purpose: The purpose of this study was to compare the accuracy of fit of Co-Cr full arch screw-retained implant-supported fixed dental prosthesis fabricated among three different methods: conventional casting, milling, and additive manufacturing technology. Materials and methods: A master model of a completely edentulous mandible with five internal connection implants was utilized. Thirty full arch Co-Cr screw-retained implant-supported frameworks were fabricated by three different methods: conventional casting, milling, and additive manufacturing (AM) technology. The marginal fit was measured using a coordinate measuring machine in x-, y-, and z-axes, as well as the three-dimensional discrepancy. The casting group were measured twice: before the adaptation procedure and again after the adaptation procedure (sectioning and laser welding). For comparisons of marginal fit of frameworks between different groups one-way analysis of variance and Games Howell test was used. Paired t-test was used to compare cast frameworks before and after adaption. Results: There were statistically significant differences in marginal fit and width distortion between groups (P <.05). The mean of total distortion of each group was 94.6 µm (SD 50.5 µm) for casting group before adaptation, 92.44 µm (SD 49.6 µm) for casting group after adaptation, 71.4 µm (SD 37.2 µm) for additive manufacturing group, while for the milling group the total distortion was 50.1 µm (SD 27.5 µm). Conclusion: Full arch screw-retained implant-supported frameworks fabricated with any of the three fabrication techniques using cobalt-chromium material exhibited acceptable marginal fit. Milling fabrication technique showed the most accurate marginal fit. Adaptation procedure for the cast group has significantly improved the marginal fit.